Effectiveness of a Multimodal Intervention Program for Older Individuals Presenting to the Emergency Department After a Fall in the Northern French Alps Emergency Network. (7th September 2016) - Ageron, François‐Xavier; Ricard, Cécile; Perrin‐Besson, Sophie; Picot, Françoise; Dumont, Odile; Cabillic, Sandrine; Haesevoet, Marc; Dalmon, Philippe; Gaillard, Corine; Cezard, Odile; Belle, Loïc; Couturier, Pascal
Abstract: Objective: Fall‐related visits to emergency departments (EDs) are common among older individuals. We aimed to assess effectiveness of a healthcare intervention program for the management of elderly patients admitted to EDs after a fall. Methods: Using a before–after observation method, we investigated ED healthcare staff practices related to fall‐related injuries in 2010 (period 1) and 2012 (period 2) in 13 centers participating in the Northern French Alps Emergency Network. Following the identification of initial weaknesses, several information and training tools were introduced between the two periods to improve patient management. All individuals aged 75 years or over who presented to an ED after a fall were included in the study. We reviewed the completeness and quality of medical records during both periods and compared the rate of clinical–paraclinical check‐ups performed, geriatric evaluation/assessment in the ED, and the 1‐month recurrence of visits to the ED for the same reason. Results: During period 1, a total of 2, 425 falls were recorded, while 2, 684 were reported in period 2. The 2012 medical charts contained significantly more information about risk factors than those of 2010. An electrocardiogram (64% vs. 53%; p < 0.001), biologic check‐up (65% vs. 57%; p < 0.001), balance, orthostatic hypotension, and cognitive impairment tests were more often performed in 2012. There was no change in the hospitalization rate, although short‐duration hospitalization in the ED was more frequent in 2012. Geriatrists were more often consulted by patients in 2012 (18% vs. 13%; p < 0.001) and more involved in ED evaluation and hospitalization. The intervention program had a beneficial impact on the fall recurrence rate ( n = 29 [3.6%] in period 1 and n = 17 [2.0%] in period 2; odds ratio = 0.52; p = 0.037), which significantly decreased between 2010 and 2012. Conclusions: The intervention program was associated with a decrease of fall recurrence. Further efforts should be made in EDs to ensure a sustained level of satisfactory and long‐lasting management of the elderly.